The Role of Computed Tomography Colonography in Detecting Bowel Involvement in Women With Deep Infiltrating Endometriosis: Comparison With Clinical History, Serum Ca125, and Transvaginal Sonography - Baggio, Silvia; Zecchin, Alessandro; Pomini, Paola; Zanconato, Giovanni; Genna, Michele; Motton, Massimiliano; Montemezzi, Stefania; Franchi, Massimo (Journal of computer assisted tomography, 2016)
We wanted to assess the diagnostic value of computed tomographic colonography (CTC) in recognizing bowel endometriosis in comparison with serum Ca125, transvaginal sonography (TVS), and presence of intestinal symptoms. We included in this study 92 women undergoing surgery for symptomatic DIE. Preoperative evaluation included clinical history, Ca125 serum value, and TVS. CTC was performed in 37/92 patients (40.2%), and the results were compared to the other preoperative tools and to surgical exploration, considered the clinical reference standard. Surgery confirmed bowel endometriosis in 49/92 subjects (53.3%). Presence of intestinal symptoms, serum Ca125 values, and TVS were significantly correlated to intestinal involvement, but CTC had the highest accuracy in detecting bowel endometriosis with a sensitivity of 68%, a specificity of 67%, a PPV of 81%, and a NPV of 50% (P = 0.04). CTC proved to be an accurate and low invasive imaging technique to detect DIE of the bowel and compared favorably with clinical evaluation, serum Ca125 determination, and TVS.